Effect of Compensation and Service on Employee Performance at PT. Infomedia Nusantara in Jakarta - Muhammad Ramdhan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study aims to determine the effect of compensation and tenure on employee performance at PT. Infomedia Nusantara in Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study that compensation has a significant effect on employee performance by 45.6%, hypothesis testing is obtained t count > t table or (7,432 > 1,997). The tenure significantly affects employee performance by 48.7%; hypothesis testing is obtained t count > t table or (7,909 > 1,997). Compensation and tenure simultaneously have a significant effect on employee performance with the regression equation Y = 5.936 + 0.381X1 + 0.485X2. The contribution of influence is 63.1%, hypothesis testing is obtained by F count > F table or (55,490 > 2,750).